Intent-driven intelligent orchestration for satellite-terrestrial networks：system architecture and key technologies - FAN Rongqian; CHENG Zhimi; LI Qiao; YANG Chungang; OUYANG Ying; WANG Pu (Dianxin kexue)
To meet the diverse and flexible service demands of heterogeneous networks across various industries, building an on-demand intelligent network slicing and orchestration system that integrates terrestrial and satellite networks has become a crucial direction for future network development. Through resource orchestration and logical isolation, network slicing can effectively support differentiated service requirements in satellite-terrestrial networks. Traditional network orchestration technologies in satellite-terrestrial networks often face challenges such as low orchestration efficiency, difficult resource scheduling, and poor service assurance when dealing with dynamic and complex scenarios. Intent-driven networks, leveraging natural language understanding technology and closed-loop dynamic feedback mechanisms, can provide adaptability and intelligence for satellite-terrestrial networks. Based on this, an intent-driven satellite-terrestrial network slicing orchestration architecture and its key technologies were proposed. Subsequently, an intent-driven satellite-terrestrial network intelligent orchestration experimental platform was established, which specifically demonstrated the entire process from user intent input to network slice instantiation completion. A comparison of the average instantiation time of three types of network slices was conducted to evaluate the effectiveness of the proposed intelligent orchestration system. The experimental results verified the adaptability and efficiency of intent-driven networking technology in the intelligent orchestration of satellite-terrestrial networks.